Pedagogical And Methodological Aspects Of The Formation Of Historical Thinking In A Future Teacher - Zamilova Rimma Ramilievna- (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In This research paper analyzed of various classifications of teaching methods showed that of the greatest interest for our topic are practical teaching methods that open up wide opportunities for the use of sources in history classes. Also important are the methods of stimulating and motivating learning, which include play, discussion and research lessons. For the most productive and effective use of the source in the system of higher education in history, the greatest opportunities open up when introducing methods into teaching practice that stimulate the search activity of students, namely: problem learning, the research method of teaching, as well as the partial search method. At the same time, the acquaintance of future history teachers with modern scientific research, unsolved problems can intensify the process of assimilating new knowledge, help consolidate already received information, and also significantly increase the efficiency of work with sources.